EDUCATIONAL PROJECT AS A MEANS OF ACTIVATING THE COGNITIVE ACTIVITY OF SENIOR STUDENTS (Pedagogy of Higher and Secondary Education, 2009)
This article deals with the essence of the educational project , and its mutantiation in the works of scientists and teacher. It is underlined the portance of the usage of a method of the projects and its practical importance ar one of the ways of increasing of the educational of the senior pupils.